Outcomes Following Healing Response in Older, Active Patients: A Primary Anterior Cruciate Ligament Repair Technique - Steadman, J. Richard; Matheny, Lauren M.; Briggs, Karen K.; Rodkey, William G.; Carreira, Dominic S. (The Journal of Knee Surgery, 2012)
The purpose of this study was to document outcomes following the healing response procedure for treatment of complete, proximal anterior cruciate ligament (ACL) tears in a mature, active population. Healing response is an all-arthroscopic procedure that preserves the native ACL and makes use of an arthroscopic awl with a 45-degree angle to make holes in the femoral attachment of the ACL and in the body of the ACL. Patients were included in this IRB-approved study if they were ≥40 years old, had a complete proximal ACL tear, and who had healing response within 6 weeks of initial injury. In this study 48 patients (35 females, 13 males) with an average age of 51 years (range: 41 to 68 years) underwent the healing response procedure. Of these four female patients (8.9%) required subsequent ACL reconstruction. Mean time to ACL reconstruction was 34.5 months (range, 14.3 to 61.2 months). Of the 44, 41 patients (93%) had minimum of 2-year follow-up at an average of 7.6 years (range, 2.2 to 13.4 years). Average preoperative Lysholm score was 54 (range, 10 to 82) and improved to an average of 90 postoperatively (p = 0.001). Median Tegner Activity Scale at follow-up was 5 (range, 2 to 9). Median patient satisfaction was 10 (range, 4 to 10). Higher patient satisfaction was correlated with increased Lysholm score at follow-up (rho = 0.39, p = 0.02). Tegner Activity Scale was associated with postoperative Lysholm score (rho = 0.35, p = 0.04). This study demonstrates the effectiveness of the healing response procedure to allow patients to return to high levels of recreational activity and to restore knee function to normal levels. In a select group of mature patients with acute proximal ACL tears, the healing response procedure is an effective treatment technique.
Keywords: anterior cruciate ligament; healing response; primary repair